The Relationship of Parental Support Models with Children's Achievement Motivation at SSB Hunter Rembang Judging from Parents' Work - Redondo Sakti Adi Pramudya; Anugrah Nur Warthadi; Muhad Fatoni (UNIB Press, 2024)
The aim of this study was to identify the support model provided by parents to their children participating in SSB Hunter Rembang, to analyze the relationship between the type of parental work and the support model provided, and to determine the impact of parental support on performance and development child at SSB Hunter Rembang. In this research, researchers used a type of research with a quantitative approach. The method used in this research is method descriptive with data collection techniques in the form of questionnaires, the sample used in this research was 20 of the children's parents SSB Hunter Rembang. The sampling technique in this research used total sampling. The percentage of parental support in supporting children who excel at SSB Hunter Rembang is 60% in the very supportive category. Different types of parental work do not reduce children's achievements in football. Parental employment influences the model of support provided to children at SSB. Diverse and comprehensive support from parents has been proven to have a positive impact on children's development and performance in football. Therefore, it is important for SSB to develop programs that can assist parents in providing optimal support for their children.